1986
DOI: 10.1016/0005-2760(86)90173-6
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the LDL receptor activity in the human hepatoma cell line Hep G2 by high-density serum fractions

Abstract: The regulation of the LDL receptor activity in the human hepatoma cell line Hep G2 was studied. In Hep G2 cells, in contrast with fibroblasts, the LDL receptor activity was increased 2.5-fold upon increasing the concentration of normal whole serum in the culture medium from 20 to 100% by volume. Incubation of the Hep G2 cells with physiological concentrations of LDL (up to 700 micrograms/ml) instead of incubation under serum-free conditions resulted in a maximum 2-fold decrease in LDL receptor activity (10-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 43 publications
4
28
1
Order By: Relevance
“…HepG2 cells also have higher absolute levels of LDL receptor mRNA than fibroblasts, but both cell lines show a similar degree of upregulation in response to LPDS (47). However, in HepG2 cells the receptor number is differentially increased relative to the receptor number in fibroblasts in response to several stimuli such as taurine, estrogen, and high density lipoproteins, all of which are believed to increase LDL receptor synthesis by depleting the cells of cholesterol (46,48,49). HepG2 cells also respond to a plasma component that stimulates receptor synthesis without a corresponding cellular cholesterol depletion whereas fibroblasts are unresponsive (50).…”
Section: Discussionmentioning
confidence: 99%
“…HepG2 cells also have higher absolute levels of LDL receptor mRNA than fibroblasts, but both cell lines show a similar degree of upregulation in response to LPDS (47). However, in HepG2 cells the receptor number is differentially increased relative to the receptor number in fibroblasts in response to several stimuli such as taurine, estrogen, and high density lipoproteins, all of which are believed to increase LDL receptor synthesis by depleting the cells of cholesterol (46,48,49). HepG2 cells also respond to a plasma component that stimulates receptor synthesis without a corresponding cellular cholesterol depletion whereas fibroblasts are unresponsive (50).…”
Section: Discussionmentioning
confidence: 99%
“…Based upon studies with HepG2 cells [38], it was suggested that in liver the less efficient down-regulation, compared to extrahepatic cells, of LDL receptors by LDL, might be related to the intracellular processing of cholesterol. The more effective down-regulation observed by feeding 2% cholesterol [lo, 391, might then be explained by the more rapid processing system coupled to p-VLDL uptake.…”
Section: Fig 9 Accumulation Of 3h Radioactivity In Control and Chlomentioning
confidence: 99%
“…LDL, low-density lipoprotein ; a-VLDL, cholesteryl ester-rich P-migrating very-low-density lipoprotein; PMA, 4p-phorbol 12-myristate 13-acetate; PKC, protein kinase C ; ACAT, acyl-CoA :cholesterol acyltransferase ; DMEM, Dulbecco's modified eagle medium. specific metabolic functions including LDL receptors [7, 81, a similar regulatory phenomenon is reported for the regulation of the LDL-receptor activity, as with human liver cells [9]. It was speculated that the inability of LDL to block LDLreceptor synthesis completely, would allow the liver to take up LDL even at high blood-LDL levels [6].…”
mentioning
confidence: 91%